The Interplay between Musical and Linguistic Aptitudes: A Review - Milovanov, Riia; Tervaniemi, Mari (Frontiers in Psychology, 2011)
According to prevailing views, the brain organization is modulated by practice, e.g., during musical or linguistic training. Most recent results, using both neuropsychological tests and brain measures, revealed an intriguing relationship between musical aptitude and linguistic abilities, especially in terms of second language pronunciation learning skills. These findings, together with their implications, will be introduced and elaborated in our review.